Implementasi Moderasi Beragama Guru Pendidikan Agama Islam di Sekolah Dasar Kota Bengkulu - Sundari, Siti; Hidayat, Wahyu; Hairiyanto, Hairiyanto (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to examine the implementation of religious moderation by Islamic Religious Education (PAI) teachers in Elementary Schools in Bengkulu City. Religious moderation is an approach that emphasizes the importance of a middle attitude, tolerance, and respect for differences in practicing religious teachings. This study uses a qualitative method with a case study approach at SDN 41 Bengkulu City. Data were collected through in-depth interviews with PAI teachers, classroom observations, and analysis of related documents. The results of the study indicate that PAI teachers at SDN 41 Bengkulu City have implemented various strategies to promote religious moderation, including through multicultural education, extracurricular activities, attitude and character development, family and community approaches, and creating an inclusive school environment. Teachers are also active in participating in professional training and discussions to improve their understanding of religious moderation. The implementation of religious moderation in this school has a positive impact on students' attitudes and behavior, creating a harmonious atmosphere and respecting differences. However, this study also found several challenges, such as limited resources and resistance from some parents. Therefore, further support is needed from the school, parents, and the community to ensure the sustainability and effectiveness of the religious moderation program.